(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2025)
The article presents a study of model lawmaking in the Commonwealth of Independent States, including the Model Law ‘On the Prosecutor’s Office’, in the context of legal ideas, grounds and objectives of its development, influence on the domestic legislation of the Commonwealth member states. The purpose of the study is to determine the role of supranational regional rulemaking in regulating prosecutorial supervision of law enforcement. The author used such special scientific methods as legal hermeneutics, formal legal, historical and legal, comparative legal. The result of the study was a retrospective identification of the social and state demand for maintaining supervision over the implementation of laws within the competence of the prosecutor’s office during the transition period, expressed in the model regulation of the activities of the prosecutor’s office, as well as the definition of the tracks of transformation of the normative regulation of prosecutorial supervision over the implementation of laws in the CIS.